Influence of heat pipe assisted terminal cooling on the thermal behavior of a large prismatic lithium-ion cell during fast charging in electric vehicles. (April 2021) - Kleiner, Jan; Singh, Randeep; Schmid, Michael; Komsiyska, Lidiya; Elger, Gordon; Endisch, Christian
Graphical abstract: Highlights: Comparison of thermal effects during commonly used fast charging profiles. Novel heat pipe based passive terminal cooling concept is proposed. Impact of terminal cooling during fast charging is investigated. Heat pipes reduce terminal/jelly roll temperature by 50 °C/4 °C during boost charging. Thermal inhomogeneities of a cell in a module arrangement are reduced by heat pipes. Abstract: Lithium-ion based battery systems are a vital part of electric vehicles. Due to limited driving range accompanied by long charging times, manufactures focus on fast charging introducing serious challenges for the battery. Even if improved charging procedures have been discussed widely, little attention has been paid so far to the thermal behavior of larger automotive cells, especially in module arrangements. Therefore, the thermal behavior of a large prismatic cell during fast charging at electric vehicle conditions is investigated for common profiles such as constant-, pulse-, and boost charging. Revealing the necessity of an improved cooling, in this work, a novel heat pipe based terminal cooling concept in addition to conventional bottom cooling is investigated experimentally and by simulation. Therefore, a 3D electro-thermal model is developed predicting the cell temperature behavior at electric vehicle boundary conditions. After successful experimental validation with a prototype based on a prismatic 25 Ah cell, the effects of the proposed heat pipe cooling concept on the fast charging profiles are investigated in detail. Investigating various fast charging profiles and module scenarios, a decrease of the jelly roll temperature by a maximum of 4.3 °C and a reduction of thermal inhomogeneities are obtained, which reduces uneven aging.